2022
DOI: 10.1111/tpj.15707
|View full text |Cite
|
Sign up to set email alerts
|

CiKN1 and CiKN6 are involved in leaf development in citrus by regulating CimiR164

Abstract: Leaf shape is an important agronomic trait that is involved in plant photosynthesis, flowering, disease resistance, and yield. In recent years, many leaf shape-related genes have been identified in model plants, but the precise regulatory network of leaf shape development remains unclear, particularly in woody plants. Transcriptome analysis of trifoliate orange and lemon leaves revealed that two citrus Knotted1-like (CiKN1 and CiKN6) genes might participate in leaf development. Overexpression of CiKN1 displays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…KNOX possesses homologous heterotypic structural domains, and it belongs to the three-amino-acid-loop-extension ( TALE ) family, which plays important roles in the maintenance of cellular totipotency and the regulation of leaf development [ 35 ]. KNOX family transcription factors underlie lobed leaf morphogenesis in multiple plants such as Lilium tsingtauense [ 36 ], citrus [ 37 ], barley [ 38 ], and Arabidopsis [ 35 , 39 , 40 ]. In lettuce, LsKN1 not only binds the promoter of LsPID to up-regulate the synthesis of growth hormone but also binds specifically to the LsAS1 promoter to down-regulate LsAS1 expression and synergistically regulate the formation of palmately lobed leaves [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…KNOX possesses homologous heterotypic structural domains, and it belongs to the three-amino-acid-loop-extension ( TALE ) family, which plays important roles in the maintenance of cellular totipotency and the regulation of leaf development [ 35 ]. KNOX family transcription factors underlie lobed leaf morphogenesis in multiple plants such as Lilium tsingtauense [ 36 ], citrus [ 37 ], barley [ 38 ], and Arabidopsis [ 35 , 39 , 40 ]. In lettuce, LsKN1 not only binds the promoter of LsPID to up-regulate the synthesis of growth hormone but also binds specifically to the LsAS1 promoter to down-regulate LsAS1 expression and synergistically regulate the formation of palmately lobed leaves [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in C. clementina showed that SPL11 (annotated as CiSPL11 in the study) positively regulates the expression of CiKN6 , a citrus homolog of KNOTTED1-LIKE HOMEOBOX ( KNOX ) family genes, by binding to its promoter. Furthermore, the study showed that CiKN6 complexes with CiKN1, which in turn suppresses the expression of miR164a by binding to its promoter and modulates leaf development in citrus (Zeng et al 2022 ). In the current study, based on their relatively unique tissue expression pattern, we chose SPL5 , SPL9 , and SPL11 orthologs from Kumquat for their functional assessment.…”
Section: Discussionmentioning
confidence: 99%
“…ngaltri, a trimutant with NGAL1-3 function loss, showed an enhanced dentate leaf margin phenotype, indicating that NGALs were involved in leaf margin development (Shao et al, 2020). In addition, Zeng et al (2022) studies on Citrus reticulata Blanco leaves also found that CiKN1 and CiKN6 have a significant impact on citrus leaf morphological development, CiKN1 and CiKN6 regulate the molecular mechanism of citrus leaf development, and they can combine with each other to form complexes. By binding to the miR164a promoter, it inhibits the expression of CimiR164a, thereby playing a role in the regulation of leaf development through the miR164a-CUC2 pathway (Zeng et al, 2022).…”
Section: Effects Of Genes On Leaf Shape During Leaf Developmentmentioning
confidence: 99%
“…In addition, Zeng et al (2022) studies on Citrus reticulata Blanco leaves also found that CiKN1 and CiKN6 have a significant impact on citrus leaf morphological development, CiKN1 and CiKN6 regulate the molecular mechanism of citrus leaf development, and they can combine with each other to form complexes. By binding to the miR164a promoter, it inhibits the expression of CimiR164a, thereby playing a role in the regulation of leaf development through the miR164a-CUC2 pathway (Zeng et al, 2022).…”
Section: Effects Of Genes On Leaf Shape During Leaf Developmentmentioning
confidence: 99%